Archief Prof. Dr. W.H. de Vriese (1806-1862) : betreffende zijn onderzoek naar de kultures in Nederlands-Indië, 1857-1862, met retroacta vanaf 1817 - Vriese, W. H. de (Willem Hendrik), 1806-1862 (1817)
Letters between de Vriese and the Ministerie van Koloniën; preliminary reports submitted to the governor general, with observations and recommendations covering European and native agriculture in the Dutch East Indies, including a range of tropical products.